“Ya Biladi, Aidati”: Woman and Homeland in the Work of Sami Michael - Shimony, Batya (MiKAN, 2012)
This essay offers an interpretation of the metaphor of Woman as Homeland (and vice versa) in three of Sami Michael’s novels: All Men are Equal but Some are More (1974), Water kissing Water (2001) and Aida (2008). The appearance of this metaphor in Michael’s work represents the struggle of the Mizrahi immigrant protagonist to be both part of the Israeli Meta-Narrative and parted from it. The expressions of this metaphor in Michael’s novels are dual and built around the tension between a symbolic-colonialist paradigm on the one hand, and a concrete-substantive one on the other. This tension is maintained throughout all three novels with the alternating predominance of one paradigm or the other. The alternation is influenced by the passing of time and by the change in attitude towards the “Other” in Israeli culture and society.